The Effect of Trust and Teamwork on Employee Performance Through Organizational Commitment as an Intervening Variable in Company - Abdul Aziz; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of trust and teamwork on employee performance through organizational commitment as an intervening variable on CV. Bhagaskara Sinarmulya. The approach used in this research is a quantitative approach. The population in this study were 43 employees. The sampling technique used by the researcher is non-probability sampling with sampling using a saturated sampling technique, with a sample of 43 employees. Analysis using SmartPLS 3.0. The results obtained that teamwork affects employee performance, trust does not affect organizational commitment, teamwork affects organizational commitment, trust has no effect on employee performance through organizational commitment as an Intervening variable, and teamwork has an effect on employee performance through organizational commitment as an Intervening variable